Secondary care consultant clinicians’ experiences of conducting emergency care and treatment planning conversations in England: an interview-based analysis - Frances Griffiths; Gavin D Perkins; Anne-Marie Slowther; Karin Eli; Claire Hawkes; Keith Couper (BMJ Open)
Objective To examine secondary care consultant clinicians’ experiences of conducting conversations about treatment escalation with patients and their relatives, using the Recommended Summary Plan for Emergency Care and Treatment (ReSPECT) process.Design Semi-structured interviews following ward round observations.Setting Two National Health Service hospitals in England.Participants Fifteen medical and surgical consultants from 10 specialties, observed in 14 wards.Analysis Interview transcripts were analysed using thematic analysis.Results Three themes were developed: (1) determining when and with whom to conduct a ReSPECT conversation; (2) framing the ReSPECT conversation to manage emotions and relationships and (3) reaching ReSPECT decisions. The results showed that when timing ReSPECT conversations, consultant clinicians rely on their predictions of a patient’s short-term prognosis; when framing ReSPECT conversations, consultant clinicians seek to minimise distress and maximise rapport and when involving a patient or a patient’s relatives in decision-making discussions, consultant clinicians are guided by their level of certainty about the patient’s illness trajectory.Conclusions The management of uncertainty about prognoses and about patients’ emotional reactions is central to secondary care consultant clinicians’ experiences of timing and conducting ReSPECT conversations.